Autophagy-mediated regulation of neutrophil inflammatory responses and its relevance to central nervous system diseases - Li, Yuliu; Tan, Yiqing; Zuo, Wei (Frontiers in Aging Neuroscience, 2025)
Autophagy is an intracellular degradation system, which plays a crucial role in regulating the inflammatory functions of neutrophils. Neutrophils, as crucial immunological phagocytes, are integral to inflammatory responses. In central nervous system diseases, neutrophils’ malfunction is closely associated with disease progression. Autophagy in neutrophils is highly conserved and plays a crucial regulatory role in both the biological functions and pathophysiological processes of neutrophils. In this review, we comprehensively explore the mechanisms of autophagy and its regulatory roles in various aspects of neutrophil biology, including the neutrophil life cycle, extracellular net traps (NETs) formation, degranulation, migration and adhesion, and phagocytosis. We also analyze the role of neutrophil autophagy in different central nervous system diseases such as Alzheimer’s disease, stroke, and neuroglioma. Regulating autophagy to control neutrophil inflammatory functions may emerge as a novel therapeutic strategy for treating central nervous system disorders.